2010
DOI: 10.1038/ng.568
|View full text |Cite
|
Sign up to set email alerts
|

New loci associated with kidney function and chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 Caucasian individuals from 20 population-based studies to identify new susceptibility loci for reduced renal function, estimated by serum creatinine (eGFRcrea), cystatin C (eGFRcys), and CKD (eGFRcrea <60 ml/min/1.73m2; n = 5,807 CKD cases). Follow-up of the 23 genome-wide sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
702
8
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 719 publications
(762 citation statements)
references
References 66 publications
31
702
8
4
Order By: Relevance
“…Data from other complex-trait studies indicate that disease-causing genetic variants are localized to regulatory regions in disease-relevant cell types, altering transcription factor binding and downstream quantitative expression of target genes. 12 This has also been shown for the CKDassociated locus at chromosome 16. Risk variants at this locus are associated with higher UMOD (MIM: 191845) transcript levels.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Data from other complex-trait studies indicate that disease-causing genetic variants are localized to regulatory regions in disease-relevant cell types, altering transcription factor binding and downstream quantitative expression of target genes. 12 This has also been shown for the CKDassociated locus at chromosome 16. Risk variants at this locus are associated with higher UMOD (MIM: 191845) transcript levels.…”
Section: Introductionmentioning
confidence: 66%
“…When compared to other traits (digestive, nervous, immune system diseases, cardiovascular, body measurement, biological processes, and other diseases), we found a significantly greater overlap between kidney eSNPs and polymorphisms that are associated with kidney function. 13,16,17,54 These results indicate that genetic variants associated with kidney function and CKD are enriched in our eQTL studies and likely drive gene expression changes in the kidney.…”
Section: Kidney Eqtl Highlights the Genetics Of Disease Traitsmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition to the de novo identified podocyte-specific genes, genes that have been shown by genetic or functional studies to be causally involved in hereditary glomerular diseases and chronic progressive renal failure, including DACH1 (nanodissection rank 184) (Köttgen et al 2010), APOL1 (rank 185) (Genovese et al 2010;Kopp et al 2011), VEGFA (rank 247) (Eremina et al 2008;Köttgen et al 2010), and MYH9 (rank 260) (Kao et al 2008;Kopp et al 2008), were ranked highly by our method. During the preparation of this manuscript, MYO1E (rank 75) was reported to be associated with autosomal-recessive, glucocorticoid-resistant nephrotic syndrome (Mele et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic approaches identified novel players in renal fibrosis (157), such as the homeodomain interacting protein kinase 2 (HIPK2) in HIV transgenic mice (158). In patients with chronic kidney disease or glomerulosclerosis, genome-wide association studies (GWAS) identified several susceptibility loci (159)(160)(161), including in genes for myosin heavy chain 9 (MYH9) and uromodulin (Tamm-Horsfall protein, UMOD). Both proteins are expressed in TECs, the latter exclusively.…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%